PENGARUH PENGGUNAAN MEDIA SPINNING WHEEL BERBANTUAN KANCING WARNA TERHADAP HASIL BELAJAR OPERASI HITUNG PERKALIAN SISWA KELAS III SD SWASTA PELANGI MEDAN - Nanda Amalia Batubara; Elvi Mailani; Wildansyah Lubis; Nur Hudayah Manjani; Putra Afriadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using a spinning wheel learning media assisted by colored buttons on students’ learning outcomes in multiplication operations. This research employed a quantitative approach with a quasi-experimental design using a pretest–posttest nonequivalent control group design. The study was conducted at SD Swasta Pelangi Medan in the academic year 2025/2026. The population consisted of all third-grade students, with class III-A as the experimental group and class III-B as the control group. Data were collected through pretest and posttest instruments that had been validated and tested for reliability. The data analysis technique included prerequisite tests (normality and homogeneity) and hypothesis testing using an independent sample t-test. The results showed that the average posttest score of the experimental class (80.42) was higher than that of the control class (61.88), with an improvement of 32.50 compared to 21.05. The hypothesis test results indicated a significance value of less than 0.05 (Sig. < 0.001), meaning that there was a significant effect of the spinning wheel media assisted by colored buttons on students' learning outcomes. Thus, the use of interactive learning media can improve students’ understanding, engagement, and learning outcomes in multiplication material.